The Role of Project Governance in Enhancing the Sustainability of Youth Empowerment Projects in Makueni County, Kenya - Ambrose Kyalo Kaumbulu (Contemporary Research in Business, Management and Economics Vol. 9, 2024)
This study investigated the relationship between project governance and sustainability of Youth Empowerment Projects in Kenya Context. The literature indicates that the sustainability of initiatives is contingent upon the efficient governance of said programs and the wide range of stakeholders involved. Research has shown that project governance results have both major and insignificant effects on sustainability; however, these studies lack empirical support in the Kenyan context. In light of this, the study examined the connection between project governance and youth empowerment project sustainability in the Kenyan setting. The study adopted both descriptive and explanatory research designs. Descriptive research design enables the researcher to apprehend a population’s possible behaviour, characteristics, values and test hypotheses. From a survey of 196 respondents who were project managers and youth leaders involved in Youth Empowerment Projects, data were collected and thereafter analysed using both descriptive and inferential statistics. The findings from the analysis revealed that the composite construct of project governance significantly predicted sustainability of Youth Empowerment Projects in Kenyan context (R = .863, R2 =.745, p = 0.000). In addition, each of the variables that made up the composite construct of project governance had significant effect on sustainability of Youth Empowerment Projects (stakeholder management: \(β\) = .173, t = 2.313, p = 0.022; governance structure: \(β\) = .659, t = 8.159, p = 0.000; project team diversity: \(β\) = .298, t = 3.728, p = 0.000). The descriptive analysis of variable of this study indicated that the aggregate mean and standard deviation scores for each of the variable of interest show that the respondents were in agreement with the practices relating to the construct of project governance. As a result of these factors greatly enhancing the sustainability of the established projects, the study concludes and advises stakeholders in Youth Empowerment Projects, such as Kenyan county governments and non-governmental organizations, to implement efficient project governance structures. These structures should include stakeholder management mechanisms, appropriately established governance structures, and strategies to improve project quality.